Hungarian Monitoring, 9 April 1989 . [Magyar rádiófigyelő], 1989. április 9 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - Gorbachev's visits to Cuba and the UK - Agreement reached in Polish politics - Yugoslavia's domestic situation - Wars in Namibia Domestic Affairs: - Brunó F. Straub in Moscow - Pauline religious order - 1990 elections? Economy: - Fridge syndrome: Hungarian shoppers in Austria Külpolitika: - Gorbacsov kubai és angliai látogatása - Megegyezés a lengyel belpolitikában - Jugoszláv belső helyzetkép - Harcok Namíbiában Belpolitika: - Straub F. Brúnó Moszkvában - A pálos szerzetesrend - Választás 1990? Gazdaság: - Hűtőláda szindróma: magyar bevásárlók Ausztriában